2022
DOI: 10.3390/lubricants10110309
|View full text |Cite
|
Sign up to set email alerts
|

Flooding Application of Vegetable- and Mineral-Based Cutting Fluids in Turning of AISI 1050 Steel

Abstract: The use of cutting fluids during machining processes remains one of the main challenges toward greener manufacturing, mainly when applied by flooding. The use of vegetable-based cutting fluids stands out as one of the alternatives toward more sustainability by making the process eco-friendlier without much impact on the economic aspects of the chain. In this paper, the performance of two vegetable-based cutting fluids applied by flooding was compared to one mineral-based during the turning process of the AISI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
1
0
1
Order By: Relevance
“…Deneylerde iki bitkisel bazlı ve bir mineral bazlı kesme sıvısı kullanmışlardır. Deneyler sonrasında iki bitkisel bazlı kesme sıvısının mineral bazlı kesme sıvısına göre daha iyi sonuçlar verdiğini belirtmişlerdir [7]. Carvalho ve diğerleri, AISI 1050 çeliğinin tornalanmasında bitkisel bazlı kesme sıvılarının performansını değerlendirmişlerdir.…”
Section: Kesmeunclassified
“…Deneylerde iki bitkisel bazlı ve bir mineral bazlı kesme sıvısı kullanmışlardır. Deneyler sonrasında iki bitkisel bazlı kesme sıvısının mineral bazlı kesme sıvısına göre daha iyi sonuçlar verdiğini belirtmişlerdir [7]. Carvalho ve diğerleri, AISI 1050 çeliğinin tornalanmasında bitkisel bazlı kesme sıvılarının performansını değerlendirmişlerdir.…”
Section: Kesmeunclassified
“…In the case of biolubricants under MQL conditions, Safie et al investigated rice bran oil, neem oil, and castor oil and showed some benefits with castor oil [11]. Compared with mineral cutting fluid, vegetable-oil-based emulsion can feature better properties for the turning of AISI 1050 steel by improving machinability as shown by Carvalho et al [12].…”
Section: Introductionmentioning
confidence: 99%